PENGARUH KARAKTERISTIK INDIVIDU, KEPEMIMPINAN DAN DISIPLIN KERJA PEGAWAI TERHADAP KINERJA DENGAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERASI(studi kasus pegawai Universitas Semarang) - Aditya Kukuh Wicaksono; Indarto; Yuli Budiarti (Sustainable Business Journal, 2025)
Employee performance is a strategic factor for the sustainability and development of an organization. This study aims to analyze the influence of individual characteristics, leadership, and work discipline on employee performance with the work environment as a moderating variable at the University of Semarang (USM). The underlying problem of this study is the suboptimal completion of organizational activities on time, which impacts overall performance. The study population consisted of 257 USM employees, with a sample of 72 employees selected through a purposive sampling method. Data analysis was conducted using multiple linear regression, t-test, coefficient of determination, and path analysis. The results showed that individual characteristics, leadership, and work discipline have a positive and significant effect on employee performance. In addition, the work environment was proven to act as a moderating variable that strengthens the influence of individual characteristics, leadership, and work discipline on employee performance. These findings emphasize the importance of creating a conducive work environment to support continuous improvement of employee performance at the University of Semarang.